Alternate Light Source Findings of Common Topical Products. Issue 3 (July 2016) - Pollitt, Erin N.; Anderson, Jocelyn C.; Scafide, Katherine N.; Holbrook, Debra; D'Silva, Glynis; Sheridan, Daniel J.
Abstract : ABSTRACT: Background: One of the important roles of a forensic clinician is to perform examinations of patients who are victims and suspects of crime. Alternate light source (ALS) is a tool that can improve evidence collection and enhance visualization of injuries. The purpose of this study was to examine if commonly used topical products fluoresce or absorb when examined with an ALS. Second, we aimed to identify patient and examination variables that may impact findings.Methods: A convenience sample of 81 subjects was used. After the application of 14 over-the-counter products, researchers observed the participants' skin with an ALS under 18 combinations of wavelengths and colored filters.Results: Of the 14 products viewed ( n = 1458 observations per product), six were found to fluoresce under alternate light in more than 40% of observations, five fluoresced in 1%–10% of observations, and three fluoresced less than 1% of the time. One product (a makeup product) absorbed ALS light consistently (81%), and a second (a sunscreen product) absorbed in 7%, whereas the remaining 12 products produced absorption findings in less than 1% of observations. In generalized mixed linear models, absorption findings were more commonly identified in participants with light or medium skin tones when compared with those with dark skin tones.Discussion: These results suggest that the presence of topical products may impact ALS findings. A thorough forensic clinical assessment should include a documented history, including assessment of potential sources of findings, to aid in interpretation.